Language, Status Planning, And Political Stigma In Leila S. Chudori’s Namaku Alam - Made Eva Trisnadewi (Indonesian Postgraduate Foreign Language Education Association, 2026)
This study aims to deeply analyze the role of language as an instrument of language planning in the formation and maintenance of political stigma against the descendants of political prisoners (tapol) during the New Order era, as reflected in Leila S. Chudori's novel Namaku Alam. While previous studies have explored the novel’s historical themes, there remains a significant research gap regarding how state-sponsored language planning specifically engineers the social marginalization of second-generation victims. This research offers a novel approach by integrating the framework of status planning—typically used in sociolinguistic policy studies—with literary critical discourse analysis to examine how linguistic policies dictate social hierarchy. The research data consist of excerpts from dialogue, narratives, and key terms in the novel related to political discrimination. The results show that the New Order regime successfully engineered social status through three main linguistic strategies: 1) Codification of Official Stigma: Through bureaucratic terms such as